Comparison of diagnostic tools to assess the feasibility of programmatic use of rapid diagnostic tests for onchocerciasis: A dataset from Gabon - Julienne Atsame; Jacob N. Stapley; Aditya Ramani; Romain Mourou; Ella Ntsame; Eya Efame; Ollomo-Nziengui Angue; Jean-Luc Obiang; Nils Pilotte; Katherine Gass; Maria-Gloria Basáñez (Data in Brief, 2024)
Due to the success of large-scale ivermectin mass drug administration (MDA), the aim of onchocerciasis intervention efforts have shifted from control of the disease to elimination of transmission. This has necessitated a greater understanding and comparison of the performance of diagnostic tools in hypoendemic (low prevalence) settings which had not been incorporated into large-scale MDA programmes before the goal switched from onchocerciasis elimination as a public health problem to elimination (interruption) of transmission (EOT). Data on age, sex and duration of residence were collected, prior to ivermectin treatment, across Gabon in 2015 from 5,829 participants in 67 communities from 14 districts. Skin-snip samples (for detection of Onchocerca volvulus microfilariae) were obtained from 4,350 (75 %) and blood samples (for detection of presence of IgG4 antibodies against the O. volvulus Ov16 antigen) from 4,257 of those skin-snip tested (98 %).Whole blood was tested in the field using the SD Ov16 Rapid Diagnostic Test Prototype (Ov16 RDT). Dried blood spots (DBS) were prepared for all blood-sampled individuals. After assessing DBS quality, 2,990 (70 %) samples underwent valid analysis in the lab using horseradish peroxidase (HRP) Ov16 enzyme-linked immunosorbent assay (Ov16 ELISA). The number of positive individuals varied between diagnostic tools with skin-snip microscopy, Ov16 RDT and Ov16 ELISA detecting 337/4,350 (8 %, 95 % CI =7 %–9 %), 383/4,257 (9 %, 8 %–10 %) and 348/2,990 (12 %, 10 %–13 %), respectively. Data were analysed to understand the age profiles of microfilarial and IgG4 antibody prevalence by diagnostic and mapped across Gabon.These data have reuse potential for policy makers, test manufacturers and country programmes when making determinations at community level of the suitability of using Ov16 RDT for conducting delineation mapping or evaluating the current stage of a community or, more generally, an evaluation unit along the EOT path. Further, these data are of use to transmission dynamics modellers who can fit models to these data to better understand the stage(s) in the O. volvulus lifecycle likely responsible for IgG4 antibody seroconversion in the presence of Ov16 antigen. This is crucial for incorporation of antibody prevalence as an output of onchocerciasis transmission models to permit evaluation of currently proposed serological thresholds to inform decisions about Start- or Stop-MDA in the context of onchocerciasis elimination mapping (OEM) and verification of EOT, respectively.